Reconsidering Priority Rights in the Reacquisition of Land Rules in Indonesia : A Legal Analysis Post-Termination of Right to Cultivate, Right to Build, and Right to Use - Moechthar, Oemar; Sekarmadji, Agus; Hidayat, Yogi; Anand, Ghansham (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2025)
Abstract: Land is a fundamental resource for fulfilling social and economic needs. In Indonesia, the expiration of limited land rights, namely the Right to Cultivate, Right to Build, and Right to Use, raises complex legal issues concerning both the legal status of the land and the position of former right holders. Government Regulation No. 18 of 2021 introduces the concept of “priority rights,” granting former holders the opportunity to reapply for rights over the same land. However, the regulation fails to stipulate a clear time limit or legal duration for exercising such priority. This regulatory gap has generated legal ambiguity, inconsistent interpretation, and recurring land disputes, thereby weakening legal certainty in Indonesian land governance. This study aims to analyze the normative foundation, legal implications, and temporal scope of priority rights in the context of post-expiration land tenure. The research employs a doctrinal legal method using statutory, conceptual, and case approaches. Legal materials are obtained through library research and analyzed using grammatical, systematic, and teleological interpretation to assess the validity, coherence, and effectiveness of the existing regulatory framework governing priority rights. The findings indicate that the absence of a definitive legal time frame for exercising priority rights creates a rechtsvacuum (legal vacuum), which not only undermines legal certainty but also exacerbates conflicts over land that has reverted to state control. Although the land formally returns to the state upon the expiration of the original rights, former holders retain a form of civil legal interest derived from their previous lawful tenure, which serves as a valid basis for prioritization. Keywords: Land Rights, Priority Rights, Expiration of Tenure, Legal Certainty.